Heart Failure Post-SARS-CoV-2 Infection in Children with Duchenne Muscular Dystrophy: The Additive Value of Cardiovascular Magnetic Resonance - George Markousis-Mavrogenis; Antonios Belegrinos; Aikaterini Giannakopoulou; Evangelos Karanasios; Vasiliki Vartela; Elephtheria Patsilinakou; Paul Samantis; Roser-Marie Pons; Antigoni Papavasiliou; Sophie I. Mavrogeni (MDPI AG, 2023)
In this case series, we describe the diagnosis of post-COVID-19 myocarditis in asymptomatic patients with Duchenne Muscular Dystrophy (DMD) and a mild COVID-19 disease course. These patients were referred for CMR due to electrocardiographic and echocardiographic alterations, which did not exist before COVID-19 infection. CMR identified the presence of severe myocardial inflammation in all patients based on abnormally elevated myocardial T2 ratio, late gadolinium enhancement, native T1 mapping, T2 mapping, and extracellular volume fraction. This was paired with concurrent impairment of left ventricular function. Appropriate treatment was initiated in all cases. Two of the four patients developed episodes of ventricular tachycardia during the following 6 months, and a defibrillator was implanted. Despite the mild clinical presentation, this case series demonstrates the diagnostic strength of CMR in the diagnosis and evaluation of post-COVID-19 myocarditis and serves to increase awareness of this potential complication amongst treating physicians.